Weakening of carbon sink on the Qinghai–Tibet Plateau - Tonghua Wu; Wensi Ma; Xiaodong Wu (Zenodo, 2022)
The file "Code for improved IBIS model.rar"is the improved IBIS model code applied for the paper "Weakening of carbon sink on the Qinghai–Tibet Plateau" which have been published in Geoderma. The data files include all data the paper applied in the context. : {"references": ["Tonghua Wu, Wensi Ma, Xiaodong Wu, Ren Li, Yongping Qiao, Xiangfei Li, Guangyang Yue, Xiaofan Zhu, Jie Ni, 2022. Weakening of carbon sink on the Qinghai\u2013Tibet Plateau. Geoderma, 412: 115707. DOI: 10.1016/j.geoderma.2022.115707"]}